We Begin Bombing in Five Minutes : Late Cold War Culture in the Age of Reagan - Hunt, Andrew E., 1968- (Book collections on Project MUSE., 2021)
"In the moments before his weekly radio address hit the airwaves in 1984, Ronald Reagan made an off-the-record joke: "I've signed legislation that will outlaw Russia forever. We begin bombing in five minutes." As reports of the stunt leaked to the press, many Americans did not find themselves laughing along with the president. Long a fervent warrior against what he termed the "Evil Empire," by the mid-1980s, Reagan confronted growing domestic opposition to his revival of the Cold War. While numerous histories of the era have glorified the "Decade of Greed," historian Andrew Hunt instead explores the period's robust political and cultural dissent. We Begin Bombing in Five Minutes focuses on a striking array of protest movements that took up issues such as the nuclear arms race, U.S. intervention in Central America, and American investments in South Africa. Hunt's new history of the eighties investigates how film, television, and other facets of popular culture critiqued Washington's Cold War policies and reveals that activists and cultural rebels alike posed a more meaningful challenge to the Cold War's excesses than their predecessors in the McCarthy era"--